2022
DOI: 10.1039/d2gc02237k
|View full text |Cite
|
Sign up to set email alerts
|

Hemicellulose content affects the properties of cellulose nanofibrils produced from softwood pulp fibres by LPMO

Abstract: Lytic polysaccharide monooxygenase (LPMO)-catalysed oxidation of cellulose has emerged as a green alternative to chemical modifications in the production of cellulose nanofibrils (CNFs) from wood pulp fibres. The effect of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…As the cohesion of the cellulose microfibril bundles became compromised, the never-dried LPMO-oxidized D-wood veneer could easily be mechanically disintegrated into a nanofiber suspension in a similar manner as described in our previous work of cellulose nanofibers (CNFs) production from delignified pulp fibers. [19,20] Atomic force microscopy (AFM) observation further showed that the LPMO-oxidized cellulose microfibrils were well-individualized with an average width of 3.9 ± 1.3 nm, corresponding to the width of the microfibrils in wood (Figure S2, Supporting Information).…”
Section: Densification Of Lpmo-oxidized Delignified Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cohesion of the cellulose microfibril bundles became compromised, the never-dried LPMO-oxidized D-wood veneer could easily be mechanically disintegrated into a nanofiber suspension in a similar manner as described in our previous work of cellulose nanofibers (CNFs) production from delignified pulp fibers. [19,20] Atomic force microscopy (AFM) observation further showed that the LPMO-oxidized cellulose microfibrils were well-individualized with an average width of 3.9 ± 1.3 nm, corresponding to the width of the microfibrils in wood (Figure S2, Supporting Information).…”
Section: Densification Of Lpmo-oxidized Delignified Woodmentioning
confidence: 99%
“…[13,17] This unique ability of LPMOs to modify the cellulose surface chemistry has recently been utilized in production of discrete cellulose microfibrils from wood fibers by mild mechanical disintegration. [19,20] However, much is not currently known about the specific microstructural alterations that are induced by LPMO to cellulose microfibrils assembly and wood cell wall, and how they might affect the properties of wood.…”
Section: Introductionmentioning
confidence: 99%
“…17,20 Other work has shown that LPMOs, which can oxidize cellulose, can offer a greener alternative to chemical modifications with chemicals such as TEMPO. [21][22][23] As enzyme accessibility has been shown to be a major impediment to effective cellulose modification, recent work has suggested that introducing less-organized regions in the pulp fibers, through the induction of curl, 11 might enhance the selective action of an enzyme cocktail when trying to hydrolyze the cellulose component. Although the occurrence of lignin has been shown to hinder the fibrillation of cellulose fibers, 24 removing most of the lignin via processes such as bleached kraft pulp, is economically challenging.…”
Section: Introductionmentioning
confidence: 99%
“…17,20 Other work has shown that LPMOs, which can oxidize cellulose, can offer a greener alternative to chemical modifications with chemicals such as TEMPO. 21–23…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanofibrils (CNFs) derived from various renewable resources have been extensively studied due to their intrinsic high aspect ratio, lightweight, and excellent mechanical properties, demonstrating significant potential for multifunctional biocomposites. , To fully exploit this potential by engineering the interface in CNF-based materials, surface modifications are often performed on CNFs. These modifications include 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO)-mediated oxidation, carboxymethylation, surface quaternization, lytic polysaccharide monooxygenase (LPMO) oxidation, and periodate oxidation. In both neat CNFs and CNF-based composites, the surface characteristics of CNFs dictate the interfibrillar phases and bonding, which are crucial for interfibrillar stress transfer and mechanical performance in both dry conditions and moist state. …”
Section: Introductionmentioning
confidence: 99%